Estimation of free roaming dogs population in two municipalities in Southern Brazil (Research, Society and Development, 2022)
Stray dogs are a problem for public health and animal welfare. The objective of this study was to estimate the population of stray dogs in two cities in the Metropolitan Region of Curitiba, Pinhais and Campo Magro, to subsidize future interventions and evaluate the methodology. The area of ​​the municipalities was divided into quadrants of approximately 1km² each, which were colored with 4 colors. By random sampling, quadrants were selected for counting dogs seen on public roads. Pairs of volunteers were conducted to register the animals using the Strays ID® application, including geographic coordinates, fotos and sex. Concomitantly, to define the degree of guardianship of each dog, a questionnaire was applied to the citizens. The data were compiled in the Excel program and the estimate was generated by the Survey package of the R program. In Pinhais, the estimate was 1428 dogs (from 388 to 2468, with a CI of 97.5%), more males (54%) than than females (34%) and undefined (12%). In Campo Magro, the estimate was 480 dogs (from 267 to 692, with a CI of 97.5%), also with more males (n=153, 64%) than females (27%) and undefined (9%). The predominance of males corroborates the literature. Regarding the degree of guardianship, there was a percentage of 43% in Pinhais and 47% in Campo Magro of stray dogs without an owner, a value above that observed in previous studies. The study was efficient in for define intervention priority and the methodology proved to be simple and easy to replicate.